ANALISIS PENGELOLAAN REKENING GIRO NASABAH: PENGERTIAN, FUNGSI, DAN IMPLEMENTASI AKUNTANSI GIRO DALAM OPERASIONAL PERBANKAN - Fransiska, Debora; Simaremare, Risno; Silaban, Marnisa; Siallagan, Hamonangan (Komunitas Manajemen Kompetitif, 2026)
This study aims to analyze the management of customer demand deposit accounts by examining the definition, types, functions, benefits, and accounting implementation of demand deposits in banking operations. Demand deposit accounts are unique bank deposit products due to their withdrawal flexibility through checks, giro slips, and various electronic transaction channels. Using a descriptive qualitative approach, this study reviews academic literature, banking regulations, and operational practices commonly applied in the banking industry. The findings indicate that demand deposit accounts play a strategic role in supporting customer liquidity, particularly among business entities, and serve as a major source of low-cost funds for banks through the nature of demand deposits. The various functions and benefits of demand deposits highlight their importance in modern payment systems and financial transaction efficiency. Meanwhile, the implementation of demand deposit accounting ensures proper recording, measurement, and reporting of transactions in accordance with financial accounting standards, thereby enhancing transparency and accountability in banking operations. Overall, this study concludes that effective management of demand deposit accounts not only improves banking service efficiency but also contributes to operational stability and customer trust.